Testing T cell activation-based promoters in driving a dual CAR T cell by utilizing different transcription factor binding sites - Khaniya, Asmita; Suppipat, Koramit; Tawinwung, Supannikar; Hirankarn, Nattiya (Chulalongkorn Medical Journal, 2024)
Background: Despite significant advancements in treating hematological malignancies using chimeric antigen receptor (CAR) T cell therapy, several challenges hinder its efficacy. To address the risk of disease relapse caused by antigen loss, researchers have explored approaches such as utilizing dual antigen-targeted CAR constructs. However, achieving optimal dual CAR activity necessitates ensuring the ideal expression of both CARs on the cell surface. Thus, employing T cell activation-based promoters could offer an alternative strategy, where the activation of one CAR triggers the expression of another. Objective: This study aimed to assess the efficiency of different activation-based promoters in driving the expression of dual CAR. Methods: Multiple iterations of T cell activation-based transcription factors such as the nuclear factor of (NFAT) activated T cells and nuclear receptor subfamily 4A (NR4A), were employed to induce the expression of dual CARs. The process involved designing a system where the activation of one CAR triggered the expression of another through T cell based transcription factors. This was achieved by integrating specific transcription factor binding sites into the promoter regions of the CAR genes. Upon activation of the initial CAR, the associated transcription factors were activated, leading to the expression of the secondary CAR. As a proof of concept, single chain variable fragments of CD19 and CD20 were utilized to create CD19/CD20 dual CAR T cells. The objective was to express the second CAR (CD20 CAR) upon activation of the first CAR (CD19 CAR) following binding to its corresponding antigen. In this approach, the expression of the CD19 CAR was driven by a constitutive promoter, while the expression of the CD20 CAR was regulated by a T cell activation-based transcription factor activated by the CD19 CAR. Results: This study showed that the use of eight repeats of the Nuclear receptor subfamily 4A (NR4A) promoter effectively stimulated the expression of CD20 CAR upon the detection of the antigen by the CD19 CAR after 72 h of activation. Conclusion: This study suggested the possibility of using endogenous CAR T cell-based activation-induced motifs to promote the expression of CAR T cells in a dual antigen-targeted CAR T cell platform.